Application of the Principle of Ikhtiyat in Murabahah Financing: A Case Study of BMT Malang, East Java - Irfan Hilmi; Abdel Naffati (IAIN Syekh Nurjati Cirebon, 2024)
The principle of effort is one of the strong roots of banking, a principle which states that in carrying out its functions and business activities, it is mandatory to be careful to protect public funds entrusted to it. There are at least 5 principles of the ikhtiyat role, in assessing prospective debitors, the bank must be guided by factors, such as character, capacity, capital, collateral, and economic conditions of economy. This research is qualitative. Data collection techniques are carried out by observation, interviews, and documentation study. The phenomenological approach is used to describe the deep understanding in this study. The findings of this study indicate that in general, the application of the principle of effort in mudharabah financing uses the 5c and 1i feasibility analysis (character, capacity, capital, condition, collateral, and insurance) by prioritizing the aspects of character analysis character, capacity ability and collateral which is assessed through the business income earned every month and the eligibility of the collateral given by the prospective member. The application of the ikhtiyat principle is one of the ways BMTs have positive and negative impacts in providing financing at BMT Malang, East Java so that BMTs are not allowed to only demand the achievement of targets without enforcing the principle of ikhtiyat.